Understanding HIV / AIDS through the dark lens of poverty - Brown, J.; Hendriks, H. J. (Dutch Reformed Theological Journal = Nederduitse Gereformeerde Teologiese Tydskrif, 2004)
The article highlights a process followed to bridge the gap of alienation between the church and the AIDS community in a very poor urban area of Lilongwe, Malawi. The research illuminated the fact that although it can be done, in so doing, discoveries were made regarding other essential, but unanticipated factors. Disillusionment came when the pious idea of church volunteers reaching out to assist their neighbours in need, revealed the true source of their motives, compounded by the reality and impact of abject poverty.
Free